Representasi Makna Lirik Lagu Dīn As-Salām dalam Tinjauan Teori Sastra Arab - Hanif, Sharikhul (Al-Fikru: Jurnal Ilmiah, 2022)
This study aims to analyze the theory and application of representation in Arabic literary works on the lyrics of the song Dīn As-Salām. The method used in this research is descriptive qualitative analysis research method, by giving deep meaning to an analysis. The research procedure is reading song lyrics, translating song lyrics, identifying data through elements of meaning in song lyrics, processing data, analyzing meaning, making conclusions. This research focuses on the song Dīn As-Salām which was popularized by singer from Sharhaj, United Arab Emirates, Sulaiman Al Mughani. This song tells about tolerance which was released around 2015, in Indonesia this song was popularized by Sabyan Gambus. The results of the study indicate that the lyrics of the song dna as-sālam are an imagination that the poem wants to convey in the literary work. as a whole contains the language needed for interpretation to be able to understand the intent and purpose. The meaning of the lyrics of this song provides an explanation of Islam, which is a religion of peace. Religion that teaches its people to love peace or fight for peace is not war, conflict or conflict. The word peace is in line with the meaning of the Islamic term ’salm’ which means peace or peace. The interpretation of this song requires an attitude of tolerance between human beings so that they understand each other, love and care for one another.